Summary of Research: Immunogenicity of Adalimumab Reference Product and Adalimumab-adbm in Patients with Rheumatoid Arthritis, Crohn’s Disease, and Chronic Plaque Psoriasis: A Pooled Analysis of the VOLTAIRE trials - Vibeke Strand (Rheumatology and Therapy)
Abstract This summary-of-research article presents the findings of a post hoc analysis comparing immunogenicity across the VOLTAIRE trials program, originally published in BMJ Open. Adalimumab-adbm (Cyltezo®) is approved by the US Food and Drug Administration as an interchangeable biosimilar to the adalimumab reference product (RP; Humira®). In this analysis of immunogenicity in patients who participated in VOLTAIRE-RA (NCT021372260), VOLTAIRE-CD (NCT02871635), and VOLTAIRE-PsO (NCT02850965), immune response was assessed in patients of each biosimilar and RP treatment arm at various time points, and further stratified by patient sex. Across VOLTAIRE trials, the incidence of immunogenicity parameters had similar trajectories and were highest in VOLTAIRE-PsO, followed by VOLTAIRE-CD and VOLTAIRE-RA, highlighting the effects of differences in patient populations and background medications on immune response for each indication. The same trend was observed in subgroup analyses by patient sex. These analyses show supporting evidence of the biosimilarity of adalimumab-adbm with adalimumab RP in adult patients with rheumatoid arthritis, Crohn’s disease, and plaque psoriasis. Trial Registrations: VOLTAIRE-RA, NCT021372260; VOLTAIRE-CD, NCT02871635; VOLTAIRE-PsO, NCT02850965.